Epistemic injustice: Power and the ethics of knowing - Fricker, Miranda (Oxford University Press, 2007)
In this exploration of new territory between ethics and epistemology, Miranda Fricker argues that there is a distinctively epistemic type of injustice, in which someone is wronged specifically in their capacity as a knower. Justice is one of the oldest and most central themes in philosophy, but in order to reveal the ethical dimension of our epistemic practices the focus must shift to injustice. Fricker adjusts the philosophical lens so that we see through to the negative space that is epistemic injustice. The book explores two different types of epistemic injustice, each driven by a form of prejudice, and from this exploration comes a positive account of two corrective ethical-intellectual virtues. The characterization of these phenomena casts light on many issues, such as social power, prejudice, virtue, and the genealogy of knowledge, and it proposes a virtue epistemological account of testimony. In this ground-breaking book, the entanglements of reason and social power are traced in a new way, to reveal the different forms of epistemic injustice and their place in the broad pattern of social injustice."–Book cover. Justice is one of the oldest and most central themes of philosophy, but sometimes we would do well to focus instead on injustice. This book argues that there is a distinctively epistemic genus of injustice, in which someone is wronged specifically in their capacity as a knower
https://oxford-universitypressscholarship-com.proxy.bibliotheques.uqam.ca/view/10.1093/acprof:oso/9780198237907.001.0001/acprof-9780198237907
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; justice sociale; phi4336; premier cycle; ressource en ligne; sciences humaines; thématiques; épistémologie

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires